Expression of COX-2 is associated with accumulation of p53 in pancreatic cancer: analysis of COX-2 and p53 expression in premalignant and malignant ductal pancreatic lesions - Hermanova, Marketa; Trna, Jan; Nenutil, Rudolf; Dite, Petr; Kala, Zdenek (European journal of gastroenterology & hepatology, 2008)
OBJECTIVES: Cyclooxygenase-2 (COX-2) and tumor suppressor p53 are molecules that are linked to the oncogenesis of pancreatic cancer. COX-2 represents a key modulatory molecule in inflammation and carcinogenesis, and is known to be implicated in the positive regulation of growth and tumorigenesis. Abnormal expression of p53 is common in many human neoplasms including pancreatic cancer. Recent studies demonstrated functional interactions between p53 and COX-2. The p53-dependent upregulation of COX-2 was proposed to be another mechanism by which p53 could abate its own growth-inhibitory and apoptotic effects. METHODS: In this study, we immunohistochemically analyzed the expression of COX-2 and p53 in 95 pancreatic resection specimens [adenocarcinomas, 95 lesions; pancreatic intraepithelial neoplasias (PanINs), 155; normal ducts, 70]. RESULTS: The expression of COX-2 increased progressively with the grade of ductal lesions (P<0.00001). A statistically significant difference of COX-2 expression between normal ducts and low-grade PanINs was revealed (P=0.0042). COX-2 overexpression was demonstrated in 82 PanINs (52.9%), and in 76 adenocarcinomas (80%). No significant correlation between the grade of adenocarcinoma and COX-2 expression was revealed (P=0.2). The expression of p53 again increased progressively with the grade of lesions (P<0.00001) with a significant increase in high-grade PanINs. A correlation between COX-2 and p53 expression levels in carcinomas was revealed (P=0.0002), and an accumulation of p53 was associated with COX-2 overexpression in premalignant and malignant ductal lesions. CONCLUSION: These findings confirmed the generally accepted pancreatic cancer progression model, and supported the concept of the interactive role of COX-2 and p53 in pancreatic cancer carcinogenesis, which offers opportunities for targeted therapy and chemoprevention of pancreatic cancer using COX-2 inhibitors.
Keywords: duktální karcinom slinivky břišní; Adenocarcinoma; Carcinoma, Pancreatic Ductal; nádory slinivky břišní; vývody pankreatu; prekancerózy; Humans; cyklooxygenasa 2; lidé středního věku; Disease Progression; Immunoenzyme Techniques; nádorový supresorový protein p53; Female; Aged; dospělí; Cyclooxygenase 2; senioři; lidé; Pancreatic Ducts; Adult; imunoenzymatické techniky; ženské pohlaví; Precancerous Conditions; Male; Pancreatic Neoplasms; Middle Aged; Aged, 80 and over; senioři nad 80 let; progrese nemoci; adenokarcinom; mužské pohlaví; Tumor Suppressor Protein p53